ON TAX OBLIGATORY AND TAXPAYER AND ITS IMPLICATIONS - Leo B. Barus (Journal of Tax Law and Policy, 2022)
The scarcity of normative studies related to the terminology of taxpayers and taxpayers, many developed countries use the terminology of taxpayers, and the more substance taxpayers refer to in the decisions of the Constitutional Court, it is necessary to conduct a study of the terminology of taxpayers and taxpayers in order to produce legal concepts that are ideal. al to one of these terminologies. A ius constituen-dum is needed in forming a positive law that shows the formulation of a concept in a definitive, firm, and transparent manner so that it is sufficient to use normative legal methods. The terminology of the taxpayer has not met the requirements in the form of "the definition must be clearer than the definiendum,” "must not mention the concept in its formulation,” and "must be able to switch back and forth between the concept and its formulation.” It is hoped that there will be a reform of the Tax Formal Law that changes the terminology of the taxpayer to the terminology of the taxpayer because it has a tendency to be a development hero and deserves excellent service from the regional and central tax authorities. The current tax laws and regulations use the terminology of taxpayers, not taxpayers. However, based on the results of literature, philosophical, and juridical studies, it is concluded that the ideal terminology in the tax laws and regulations in Indonesia is the taxpayer.